2019
DOI: 10.1002/acr.23833
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Structural Skeletal Muscle Health in Systemic Lupus Erythematosus–Related Fatigue: A Multimodal Magnetic Resonance Imaging Study

Abstract: Objective. To investigate the potential structural and metabolic role of skeletal muscle in systemic lupus erythematosus (SLE)-related fatigue.Methods. A case-control, multimodal magnetic resonance imaging (MRI) study was conducted. Cases were patients with inactive SLE who reported chronic fatigue. Controls were age-and sex-matched healthy members of the general population. Patients were clinically characterized and then underwent a 3T whole-body MRI scan. Resting and dynamic 31 P MRI spectroscopy of the calf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Type II fibres are responsible for fast contraction and type II fibre atrophy is associated with reduced strength and physical performance; however, whether IMAT contributes to changes in fibre type in patients with SLE is unknown. In contrsast to our findings, a previous study did not find any difference in the fat accumulation in the soleus muscle in patients with SLE 29. The explanation may be that we measured fat accumulation in a larger muscle compartment that accounts for fat between fascicles and between muscles.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Type II fibres are responsible for fast contraction and type II fibre atrophy is associated with reduced strength and physical performance; however, whether IMAT contributes to changes in fibre type in patients with SLE is unknown. In contrsast to our findings, a previous study did not find any difference in the fat accumulation in the soleus muscle in patients with SLE 29. The explanation may be that we measured fat accumulation in a larger muscle compartment that accounts for fat between fascicles and between muscles.…”
Section: Discussionsupporting
confidence: 60%
“…In contrsast to our findings, a previous study did not find any difference in the fat accumulation in the soleus muscle in patients with SLE. 29 The explanation may be that we measured fat accumulation in a larger muscle compartment that accounts for fat between fascicles and between muscles. (eg, between soleus and gastrocnemius).…”
Section: Discussionmentioning
confidence: 99%
“…This is the main hypothesis behind a study analyzing the relationship between muscle loss and systemic lupus erythematosus—related fatigue in a small sample of patients. The authors observed, via MRI, a voluntary reduced muscle contraction in subjects perceiving higher exertion, concluding toward a sarcopenia driven by fatigue, rather than the opposite 46 . The two interpretations however, instead of opposite, could be seen as a self-powered vicious cycle.…”
Section: Discussionmentioning
confidence: 96%
“…The authors observed, via MRI, a voluntary reduced muscle contraction in subjects perceiving higher exertion, concluding toward a sarcopenia driven by fatigue, rather than the opposite. 42 The two interpretations however, instead of opposite, could be seen as a self-powered vicious cycle. This finding is consistent with the literature concerning strategies to treat fatigue: physical activity has already been identified as a valid therapeutic intervention for different cancers 43,44,45 and two exploratory studies showed promising effects in subjects affected by IBD.…”
Section: Discussionmentioning
confidence: 99%